Anemia Fanconi : Review Article - Syaka, Muthiiah Khodista; Panjaitan, Vania Christy M; Gerliandi, Egi Oktarian; Dewi, Meidiana Kartika (Medula, 2024)
Fanconi anemia (AF) is a rare, multisystem genetic disorder that affects various physiological aspects, especially the bone marrow, and increases the risk of cancer, such as acute myeloid leukemia (AML) and head and neck cancer. This disease is caused by mutations in 23 genes of the FA/BRCA DNA repair pathway. This article presents the results of a literature study on FA, with a focus on etiology, pathophysiology, molecular pathology, diagnosis, risk factors, clinical symptoms, and management. Through literature study methods, the author collected information from national and international journal sources between 2012 and 2021. The etiology of FA involves mutations in 23 FA genes, with variations in carrier frequency depending on ethnic group. The pathophysiology of FA is related to the inability of cells to repair damaged DNA interstrand crosslinks (ICLs), which can lead to bone marrow failure. Molecular pathology involves the function of the FA/BRCA repair pathway and its impact on the genome. Diagnosis of FA requires clinical evaluation, molecular analysis, and bone marrow examination. Risk factors involve genetic aspects and specific carrier frequencies in ethnic populations. Clinical symptoms of FA involve anemia, infection, and somatic manifestations. Management of FA depends on the severity, with hematopoietic stem cell transplantation (HSCT) being the primary choice. HSCT from matched, nonmatched, or haploidentical donors has provided increasingly better results. This study underscores the importance of early diagnosis of FA to improve prognosis. Although HSCT is the primary treatment option, careful consideration of risks and benefits must be taken. The results of this literature study provide in-depth insight into FA, supporting appropriate monitoring and management efforts for individuals with this condition.